FALSAFAH MADURA DALAM NOVEL TANJUNG KEMARAU KARYA ROYYAN JULIAN: KAJIAN ANTROPOLOGI SASTRA - Maharani Sri Devi; Titik Maslikatin; Abu Bakar Ramadhan Muhamad; Bambang Aris Kartika; Dewi Angelina (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
The culture of an ethnic group can be known through its reflection in literary works. The Tanjung Kemarau novel by Royyan Julian tells about the complexities of the socio-cultural life of the Madurese people in Branta Pesisir Village, Pamekasan Regency, Madura. This study aims to describe the Madurese philosophy contained in the novel Tanjung Kemarau by Royyan Julian. The method used in this study is a qualitative method with descriptive analysis. This study uses the theory of literary anthropology to examine the main problem in the Tanjung Kemarau novel, namely the Madurese philosophy. The results of the study show that the Madurese philosophy reflected in the Tanjung Kemarau novel is abhântal sahâdât, smokepo' faith, apajung Èslam, (bearing creed, covered with faith, covered with Islam). Moreover, there are also found bhuppa', bhâbhu', ghuru, rato, (father, mother, teacher, and king or leader). The other phylosophy terms are abhântal ombâk, smokepo' angèn, apajung langngè', (cushioned by the waves, covered with wind, under the sky's umbrella) also Ango'an potèa tolang è tembhâng potè mata (better white bones than whites of eyes). Kar ngarkar colpè' (paw continuously pecking), Rampa' naong bâringèn korong (shady shady, banyan brackets) are stated in the novel. All the Madurese philosophy revealed in the novel describes the philosophy in the social reality of the Madurese people.